Comparison of two front-of-pack nutrition labels for Brazilian consumers using a smartphone app in a real-world grocery store: A pilot randomized controlled study - Silva, Alessandro Rangel Carolino Sales; Ni Mhurchu, Cliona; Anastácio, Lucilene Rezende (Frontiers in Nutrition, 2022)
One of the suggestions for improving the understanding of food labels is implementing front-of-pack nutrition labeling (FoPNL), where nutritional information is objectively made available to consumers. Scientific data on the best FoPNL model to be adopted for the Brazilian population is still emerging, especially in real-world purchase situations. This study aims to evaluate/compare the proposed Brazilian and Mexican FoPNL systems, on different outcome measures, using an application in dairy foods available in a supermarket aisle. This pilot randomized controlled trial in real-world purchase situation was conducted in 2021. A total of 230 participants were randomly allocated to one of the three study arms (Mexican and Brazilian FoPNL systems or control – nutritional information table and ingredients list). Using a smartphone, the participants scanned a product barcode and received the allocated FoPNL (with information about excessive added sugars, sodium, and/or saturated fat content) or the control. After, they answered questions related to our primary outcome (decision of to buy or not to buy a product) and secondary outcomes (perceived healthiness, facilitation of a quick purchase decision and identification of excess nutrients). The Mexican FoPNL system performed better in the primary outcome (3.74±1.34) and “facilitation of a quick purchase decision” (3.59±1.31), compared to the control (3.28±1.45;p=0.043 and 3.11±1.42;p=0.029). The Mexican FoPNL system performed better in supporting consumers to identify dairy foods, among the selected sample in this study, high in added sugars than the control (82.2% and 63.5% of correct answers, respectively; p=0.009). For saturated fats, the Brazilian FoPNL resulted in 93.1% of correct answers against 48.2% for the control and 58.9% for the Mexican system (p≤0.001). The Mexican FoPNL system facilitated consumer decision-making on when to buy or not to buy a selected dairy product and in helping to quickly decide which dairy products to buy, among the selected sample in this study, compared to the control. Considering the right answers of critical nutrients in excess or not, both models of FoPNL, delivered by a smartphone app, performed well.